STRUKTUR PASAR BANK DAN KINERJA BANK (Fokus Ekonomi, 2010)
This paper explains  how  bank market structure influence the bank performance. There are two Competing hyphothesis with regard to market structure and performance. The first hyphothesis is Structure Conduct Performace (SCP) and the second hyphothesis is Efficient Structure Hyphotesis (ES). According to SCP hyphothesis, the degree of competition among banks in  a market is influenced by the degree of concentration of their output among a few relatively large banks, since a more highly concentrated market  Structure is assumed to be conducive to a more effective Collusion.  ES hyphothesis stipulates that a bank which operates more efficiently than its competitors gains higher profits resulting from low operational costs. Consequenttly, differences at the level of efficiency creates  an unequal distributions of positions within the market and creates concentration.   If SCP hyphothesis found then antitrust policy shoud be taken and if ES found then increasing concentration in banking market should not be ristricted by regulatory